Genetic divergence of paddy landraces in Nanakosi micro-watershed of Uttarakhand Himalaya - Bisht, Vimla; Rao, K. S.; Maikhuri, R. K.; Nautiyal, A. R. (Journal of Tropical Agriculture, 2008)
Thirteen landraces of paddy, collected from the Nanakosi microwatershed in Almora district of Uttarakhand, were evaluated for the pattern of genetic diversity using multivariate analysis of Mahalanobis D2 statistics. These landraces formed seven distinct clusters, three with one landrace each, two with two, and the rest had three landraces each. Most landraces showed characters such as intermediate maturity, tall to medium stature, aroma, slender grain type, red or white grain colour, and had 1:1 grain to straw ratio; but they were mostly not tolerant to drought. This study reconfirms that the farmers in the focal area traditionally used landraces of paddy having ability to withstand climatic exigencies and provide not only grains but also paddy straw.